PENGENDALIAN KUALITAS PADA PROSES PERAKITAN RADIO UNTUK MEMINIMASI PRODUK CACAT - Suliawati, Suliawati; Gumay, Vita Sari (Jurnal Sistem Teknik Industri, 2017)
The development of technology in the era of globalization is currently growing rapidly where the company must be able to provide customer satisfaction with product quality. This is done to improve product quality by addressing the cause of defects in a production process. process quality control methods such as seven tools, are used to reduce the number of defects in Radio assembly. Errors caused by soldering, composing and retrieving components. Based on the use of seven tools that have been done, namely stratification, check sheet, histogram, pareto diagram, scatter diagram, cause and effect diagram, and control chart, it is found that the biggest kind of ignorance in the assembly process of Radio lies in the wrong soldering way. Based on the cause and effect diagram can be seen the factors that cause common errors in work stations. the factors that cause errors are human, method, equipment, raw materials and environment.